Journalism and political democracy in Brazil - Matos, Carolina, 1973- (Lexington Books, 2008)
Explores the process of media development and democratization in Brazil. This book is intended for those interested in Latin American and Brazilian politics, history, and media, as well as for those concerned about the role of the press in democratic tran.